Aplicación de metodologías alternativas para la clarificación del jugo de caña en la elaboración de panela granulada en la parroquia Palo Quemado del cantón Sigchos. - Velásquez Chicaiza, Darwin Javier (2023)
The main objective of this study was to determine the production of granulated panela using different concentrations and types of mucilage (balsam and prickly pear) for sugar cane juice clarification. Additionally, a filtering system for sugar cane juice prior to the cooking process was developed. A completely randomized block design with a 2*3 factorial arrangement was implemented. This design allowed for variable control and evaluation of the effect of 3 concentrations and 2 types of mucilage on sugar cane juice clarification. Analysis of the results highlighted that treatment t5 (a2 b2) with 500ml of sugar cane juice and 50g of balsam mucilage showed the best results in terms of pH (4.78), °Brix (12.15 g), acidity (0.21%), and turbidity (482.83 NTU). This treatment proved to be effective in clarifying sugar cane juice by removing impurities and improving transparency and quality of the final product. Furthermore, this study contributed to establishing the appropriate concentration and type of mucilage for sugar cane juice clarification, which is relevant for enhancing production processes in the food industry. The development of an efficient filtering system tailored to the process needs in granulated panela production aligns with the linkage function and agreement with "Maquita," and the research stems from the linkage project "Food Production and Good Practices" and can be implemented to ensure that the filtration process meets quality standards and guarantees the production of the final product.